Spinal nephroblastoma in a dog: a case report - KAMPOURI, P.; KARIKI, A.; BAKA, R.D.; PATSIKAS, M.N.; POLIZOPOULOU, Z.S. (Journal of the Hellenic Veterinary Medical Society, 2019)
The case report presents the clinical, clinicopathological, diagnostic imaging and histopathological findings of spinal cord nephroblastoma in a dog. It was admitted with a 2-week history of a “weight-bearing” lameness of the left posterior limb that evolved to paraplegia within hours. Neurological examination showed spastic paraplegia compatible with a T3-L3 spinal cord lesion. Differential diagnosis included ischemic myelopathy, myelitis and acute spinal cord compression. The spinal radiographs and cerebrospinal fluid analysis were unremarkable. Cisternal myelography indicated a focal intradural-extramedullary lesion at the level of T12 vertebra. Further diagnostic investigation was not performed because the owner decided to proceed to euthanasia. Histopathological examination of the spinal cord confirmed the diagnosis of intraspinal nephroblastoma.